Park and ride study at light rapid transit (LRT) stations in Puchong, Malaysia - GOH, Boon Hoe; Han Xiang, Phang; Choon Wah, Yuen; Byung Gyoo, Kang (International Journal of Engineering and Technology, 2018)
This paper explored the factors influencing commuter’s preferences of using park and ride (PnR), by investigating their travel mode choice behaviour, and assessing the effectiveness of PnR facilities. Binary logistic regression (BLR) was used to develop travel mode choice model which provides insight into commuter’s considerations contributing to the utilisation of PnR facility. Several scenarios were modelled to investigate the effect of policy changes on commuter’s travel mode shift, which could be essential in formulating effective strategy to promote the use of PnR. The results revealed working trip, short travel time (< 15 mins) and medium long travel distance (1–3 km), were the main considerations of commuter using PnR. The significant influencing factors were determined as travel distance from origin to departing station and from arriving distance to destination, trip purpose, frequency of using light rapid transit (LRT), education level and occupation. 3 scenarios were modelled which revealed that provision of parking subsidy, medium travel distance (around 10 km) and medium travel time (around 20 mins) encouraged commuter to use PnR while travelling in group discourage the use of PnR.